ATTINJA’ TRADITION IN BUNGUNG SALAPANG AS THE TRUST OF THE PEOPLE OF BONTORAPPO VILLAGE, JENEPONTO REGENCY - Nur Asmi Nur Asmi; Firdaus W Suhaeb; Ernawati S K (Universitas Negeri Makassar, 2026)
This study aims to find out the factors that cause the Bontorappo people to carry out the attinja' tradition in Bungung Salapang and the implementation of the attinja' tradition in Bungung Salapang as the belief of the people of Bontorappo Village. The type of research is qualitative research with a phenomenological approach. The data collection technique uses observation, interviews and documentation. Checking the validity of the data is using source triangulation. The data analysis used is data reduction, data presentation, and conclusion drawn. The theory used is the theory of social action put forward by Max Weber with the concepts of instrumental rational action, value-oriented rationality action, traditional action, and affective action. The results of the study show that 1) the factors that cause the Bontorappo people to carry out the attinja' tradition in Bungung Salapang, namely the hope that the wishes will be granted, the community's belief factor, the community's traditional factor, and to purify themselves in Bungung Salapang. 2) The implementation of the attinja' tradition in Bungung Salapang consists of 2 rituals, namely annyikko kana (binding a promise) and palappasa kana (unpromising). 1) Anyyikko kana (binding a promise) is done by tying a rope on a tree in the area around Bungung Salapang while offering attinja' or vows so that his wish can be realized. 2) Palappasa kana (releasing a promise) is carried out in Bungung Salapang by removing the rope that had been tied to a tree in the area around Bungung Salapang and bringing an offering after the requested wish is granted.